St. Lawrence Seaway And The Canadian Mineral Industry With Particular Reference To Iron Ore ? Introduction - R. B. Elver (Society for Mining, Metallurgy & Exploration, 1960)
The St Lawrence Seaway, a deep-water canal system between Montreal and Lake Ontario, was opened for navigation on April 25, 1959. Prior to the opening of the new Seaway, small boats known as canalers and a few deep-sea carriers, primarily from Norway since World War II, were the only ships able to journey past Montreal into Lake Ontario through the old Canadian St. Lawrence canal system. Thus it was necessary for many tons of bulk and general cargo to be shipped all-rail to and from Atlantic ports or to be transhipped to and from canalers. With the opening of the new Seaway, large Great Lakes bulk carriers and a much larger percentage of the world's shipping fleet are now able to sail directly from the sea to the heart of industrial North America. In this paper, the historical events leading up to the construction of the Seaway and the physical nature of the Great Lakes transportation system are briefly reviewed. Following this, an attempt is made to evaluate the effects of the new Seaway on Canada's mineral industry. Because the Seaway has been in operation for only one season, this paper must be considered only an interim report. Because of the importance of the Seaway to iron ore, this commodity will be dealt with in detail, although the effect on other mineral commodities such as coal, petroleum, nonferrous ores, iron and steel will be mentioned. At this time the author wishes to thank the various company and government officials who provided both factual information and critical opinions.